Talking to Myself, Looking in the Mirror: Insights into Language Use and Self-Representation in Personal Narratives - Sanagustín Cabrero, Andrea (Trinity College Dublin, 2024)
In 1994, Alice Kaplan put forward the term ‘language memoir’ to refer to those personal narratives written from the perspective of a life lived in a multiplicity of languages, where those languages were understood as an essential part of personal development. This dissertation uses Kaplan’s coinage as a basis to focus on the multifaceted realm of memoir writing in second languages with four main pillars of research: writing as a process and as a product, bilingualism and linguistic hybridity, cultural difference, and migration experiences. Key concepts to be explored include the performance of memory in writing, the importance of testimony and truthfulness for personal narratives, the healing of ‘exile spaces’ (Bracewell, 2002) through the choice of a second language for writing, and the experience of migration as a catalyst for self-identification. The analysis was performed on five memoirs written in English by self-described Hispanic authors living in the United States: Richard Rodriguez, Julia Alvarez, Ariel Dorfman, Ilan Stavans, and Quiara Alegría Hudes. Their base similarities (English-Spanish as a linguistic combination, as well as experiences of migrating to and from the United States) allowed for comparisons in terms of diasporic migration experiences and linguistic self-understanding, while at the same time remaining distinct enough to establish a chronology of Latinx understanding of their relationship with the United States, from the publication of Rodriguez’s memoir in 1982 to the publication of Hudes’ in 2021. This study represents the first attempt to analyse Alvarez and Hudes’ writing from the perspective of language memoirs, as well as a new conceptualisation of a group analysis of autobiographical writing that focuses on the Latin American diaspora living in the United States.